Laminate and method for producing laminate

By using graft modified polyolefins with carbodiimide groups and polymerizable double bonds, a PPS laminate with high bond strength is formed, which solves the problem of poor bondability between PPS and other resins, and realizes that in a short time Manufacture of laminated bodies with high bonding strength, suitable for high temperature environments.

CN119136983APending Publication Date: 2024-12-13MITSUI CHEMICALS INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380038463.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-26
Filing Date
2023-05-25
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the prior art, the poor bondability of polyphenylene sulfide (PPS) with other resins limits its application in laminates, especially laminates with high bond strength are difficult to achieve in a short bonding time.

Method used

A graft modification made by modifying the polyolefin from a carbodiimide monomer having a carbodiimide group and a polymerizable double bond is formed to form a bonding composition between a layer containing PPS and a bonding layer. The laminated body is manufactured by coextrusion molding, lamination molding, blow molding or coinjection molding.

Benefits of technology

A laminate with high bond strength between the PPS layer with polar groups and the bonding layer is achieved in a short bonding time (such as within 5 seconds), and the indirect bonding force of the layer is not easily reduced at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005118505050000021
    Figure BDA0005118505050000021
  • Figure BDA0005118505050000031
    Figure BDA0005118505050000031
  • Figure BDA0005118505050000091
    Figure BDA0005118505050000091
Patent Text Reader

Abstract

One embodiment of the present invention relates to: a laminate provided with a layer (A) containing polyphenylene sulfide and a bonding layer (B) containing a bonding composition, at least a part of which is in contact with the layer (A); and a method for producing the laminate. The bonding composition contains a graft-modified body obtained by modifying at least one base polymer selected from polyolefins with a carbodiimide monomer having a carbodiimide group and a polymerizable double bond, the bonding composition contains 0.1-50 mmol of carbodiimide group per 100 g of the bonding composition, and the bonding composition has a density of 0.870-0.940 g / cm3.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] One embodiment of the present invention relates to a laminate and a method for producing the laminate. Background Art

[0002] Polyphenylene sulfide (hereinafter referred to as "PPS") is used in electronic components, mechanical parts, medical parts, hot water pipes, etc. due to its high heat resistance and high chemical corrosion resistance. However, since PPS is expensive, research has been conducted on combining it with various materials.

[0003] However, it is well known that the functional groups at the terminals of PPS have poor reactivity with functional groups existing on the surfaces of other resins (for example, conventionally known maleic anhydride-modified resins), and therefore the bonding properties with other resins are poor.

[0004] Therefore, the lamination application of PPS with other materials is limited.

[0005] In order to solve such problems, Patent Document 1 discloses a laminate including a layer containing PPS and a layer at least partially in contact with the layer and made of a bonding composition containing predetermined components as a laminate having a layer containing PPS and having high bonding strength.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: International Publication No. 2017 / 104731 Summary of the invention

[0009] However, with the recent improvement in the requirements for physical properties, there is a need to realize a laminate having a higher bonding strength than the laminate described in Patent Document 1 regarding a layer containing PPS and a bonding layer. In particular, when forming a laminate by a method such as co-injection molding that cannot implement a long bonding time, there is a strong demand for the realization of a PPS laminate that exhibits high bonding strength even in a shorter bonding time.

[0010] One embodiment of the present invention provides a laminate having excellent bonding strength between a layer containing PPS and a bonding layer even in a short bonding time, and a method for producing the laminate.

[0011] Technical solutions to solve problems

[0012] The configuration examples of the present invention are as follows.

[0013] [1] A laminate comprising: a layer (A) containing polyphenylene sulfide and a bonding layer (B) containing a bonding composition,

[0014] At least a portion of the bonding layer (B) is in contact with the layer (A),

[0015] The above-mentioned bonding composition satisfies the following requirements (i) to (iii):

[0016] (i) comprising a graft modified product obtained by modifying at least one base polymer selected from polyolefins with a carbodiimide monomer having a carbodiimide group and a polymerizable double bond;

[0017] (ii) containing 0.1 to 50 mmol of carbodiimide groups per 100 g of the bonding composition;

[0018] (iii) Density: 0.870 to 0.940 g / cm 3 .

[0019] [2] The laminate according to [1], wherein the carbodiimide monomer is at least one monomer selected from the group consisting of a compound represented by the following formula (1) and a compound represented by the following formula (2),

[0020]

[0021] In formula (1), R1 is a hydrogen atom or a methyl group, R2 is an alkyl group or an aryl group which may have a substituent, and in formula (2), R3 is a hydrogen atom or a methyl group, R4 is an alkyl group or an aryl group which may have a substituent, and m is an integer greater than 2.

[0022] [3] The laminate according to [1] or [2], wherein the layer (A) is made of polyphenylene sulfide.

[0023] [4] The laminate according to any one of [1] to [3], wherein the laminate is obtained by coextrusion molding, lamination molding, blow molding or coinjection molding.

[0024] [5] A method for producing a laminate, wherein the laminate comprises: a layer (A) containing polyphenylene sulfide and a bonding layer (B) containing a bonding composition, at least a portion of the bonding layer (B) being in contact with the layer (A);

[0025] The manufacturing method comprises: step 1 of co-extrusion molding, lamination molding, blow molding or co-injection molding of a resin composition containing polyphenylene sulfide and the bonding composition;

[0026] The above-mentioned bonding composition satisfies the following requirements (i) to (iii):

[0027] (i) comprising a graft modified body formed by modifying at least one base polymer selected from polyolefins with a carbodiimide monomer having a carbodiimide group and a polymerizable double bond;

[0028] (ii) containing 0.1 to 50 mmol of carbodiimide groups per 100 g of the bonding composition;

[0029] (iii) Density: 0.870 to 0.940 g / cm 3 .

[0030] [6] The method for producing a laminate according to [5], wherein the carbodiimide monomer is at least one monomer selected from the group consisting of a compound represented by the following formula (1) and a compound represented by the following formula (2),

[0031]

[0032] In formula (1), R1 is a hydrogen atom or a methyl group, R2 is an alkyl group or an aryl group which may have a substituent, and in formula (2), R3 is a hydrogen atom or a methyl group, R4 is an alkyl group or an aryl group which may have a substituent, and m is an integer greater than 2.

[0033] [7] The method for producing a laminate according to [5] or [6], wherein the layer (A) is made of polyphenylene sulfide.

[0034] Effects of the Invention

[0035] According to one embodiment of the present invention, a laminate having excellent bonding strength between a layer containing PPS of a resin having a polar group and a bonding layer even in a short bonding time (eg, within 5 seconds) and a method for producing the same can be provided. DETAILED DESCRIPTION

[0036] "Laminated Body"

[0037] A laminate according to one embodiment of the present invention comprises a layer (A) containing PPS and a bonding layer (B) containing a bonding composition, wherein at least a portion of the layer (B) is in contact with the layer (A).

[0038] Since the above-mentioned laminate has the above-mentioned layer (B), it is possible to obtain a laminate having excellent interlayer bonding properties, and the interlayer bonding strength is not easily reduced even if the laminate is formed within a short bonding time such as within 5 seconds, or even if the laminate is heat-treated at a high temperature such as 200 to 250°C.

[0039] The laminate is not particularly limited as long as it contains the layer (A) and the layer (B). It may contain two or more layers of the layer (A) or two or more layers of the layer (B). When it contains two or more layers of the layer (A), these layers may be the same layer or different layers. In addition, similarly, when it contains two or more layers of the layer (B), these layers may be the same layer or different layers.

[0040] The above-mentioned laminate is preferably a laminate comprising layer (A) and layer (B), particularly preferably a laminate consisting of layer (A) and layer (B), or a laminate comprising layer (A), layer (B) and layer (A) in sequence, particularly preferably a laminate in which layer (A), layer (B) and layer (A) are stacked in sequence.

[0041] In addition, as a laminate including the above-mentioned layer (A) and layer (B), for example, a laminate including layer (A), layer (B), and layer (C) in this order may be sufficient.

[0042] There are no particular restrictions on the layer (C) as long as it is a layer other than layer (A) and layer (B). Examples thereof include layers containing thermoplastic resins such as metal, glass, wood, paper, cloth, polyester, polyamide, polyacetal, polycarbonate, poly(meth)acrylate, olefin polymers, polystyrene, rubber, modified fluororesin, biomass plastic, and other engineering plastics, and thermosetting resins, or layers consisting of these materials.

[0043] The laminate is not limited to the shape of a laminate film (sheet), and may be any of various known shapes such as a hollow container, a cup, and a tray.

[0044] The laminate is preferably a laminate obtained by co-extrusion molding, lamination molding, blow molding or coinjection molding from the viewpoint of easily obtaining a laminate having excellent bonding strength.

[0045] <Polyphenylene sulfide-containing layer (A)>

[0046] The layer (A) is not particularly limited as long as it contains polyphenylene sulfide (PPS), but is preferably a layer consisting (only) of PPS.

[0047] The PPS may be a polymer using only a biomass-derived raw material, a polymer using only a fossil fuel-derived raw material, or a polymer using both a biomass-derived raw material and a fossil fuel-derived raw material.

[0048] From the viewpoint of reducing environmental load (mainly reducing greenhouse gases), the PPS is preferably a polymer made from a biomass-derived raw material.

[0049] As the above-mentioned PPS, for example, a polymer formed by aromatic rings connected by sulfide bonds, i.e., branched or linear polyphenylene sulfide and copolymers thereof can be cited. Specifically, poly(p-phenylene sulfide) and poly(m-phenylene sulfide) can be cited. In addition, PPS can be a copolymer, for example, a copolymer including not only units formed by aromatic rings and sulfide bonds but also ether units, sulfone units, biphenyl units, naphthyl units, substituted phenyl sulfide units, trifunctional phenyl sulfide units, etc. in the molecule. Specifically, poly(thio-1,4-phenylene) can be cited.

[0050] Moreover, as said PPS, commercially available PPS can also be used. As commercially available PPS, FORTRON FX4382T1 manufactured by Ticona Corporation and TORELINA A900 manufactured by Toray Industries, Ltd. are mentioned, for example.

[0051] As the above-mentioned PPS, one kind may be used, or two or more kinds may be used.

[0052] The layer (A) may contain additives such as phenolic antioxidants, phosphorus antioxidants, sulfur antioxidants, metal compounds, and metal salts of higher fatty acids, which are generally used for adding to resins, as necessary, within the range not impairing the purpose of the present invention.

[0053] The additive may be an additive using only a biomass-derived raw material as its raw material, an additive using only a fossil fuel-derived raw material, or an additive using both a biomass-derived raw material and a fossil fuel-derived raw material.

[0054] The thickness of the layer (A) is not particularly limited and may be appropriately selected depending on the intended use of the laminate, but is preferably 2 to 1000 μm.

[0055] <Joint layer (B)>

[0056] The layer (B) is a layer containing a bonding composition (hereinafter also referred to as "the composition of the present invention") and can be obtained using the composition of the present invention.

[0057] The content of the composition of the present invention in the layer (B) is preferably 80 to 100% by mass, more preferably 90 to 100% by mass.

[0058] The thickness of the layer (B) is not particularly limited and may be appropriately selected depending on the intended use of the laminate, but is preferably 2 to 1000 μm.

[0059] [Joining composition]

[0060] The composition of the present invention satisfies the following requirements (i) to (iii):

[0061] (i) a graft modified product obtained by modifying at least one base polymer selected from polyolefins with a carbodiimide monomer having a carbodiimide group and a polymerizable double bond (hereinafter also referred to as "the modified product of the present invention");

[0062] (ii) containing 0.1 to 50 mmol of carbodiimide groups per 100 g of the composition of the present invention;

[0063] (iii) Density: 0.870 to 0.940 g / cm 3 .

[0064] The content of the carbodiimide group in the composition of the present invention is 0.1 to 50 mmol, preferably 0.2 to 20 mmol, more preferably 0.5 to 5 mmol per 100 g of the composition of the present invention.

[0065] When the carbodiimide group content is within the above range, the composition of the present invention can be easily obtained which can be firmly bonded to an object to be bonded, particularly a layer containing PPS, even at a low temperature at which the PPS does not thermally decompose.

[0066] The carbodiimide group content is specifically measured by the method described in the following examples.

[0067] The density of the composition of the present invention measured according to JIS K 7210 is 0.870 to 0.940 g / cm 3 , preferably 0.880 to 0.925 g / cm 3 , more preferably 0.890 to 0.920 g / cm 3 .

[0068] When the density is within the above range, the composition of the present invention can be easily obtained which can be firmly bonded to an object to be bonded, particularly a layer containing PPS, even at a low temperature at which the PPS does not thermally decompose.

[0069] The melt flow rate (MFR) of the composition of the present invention measured at 190°C and under a load of 2.16 kg in accordance with JIS K 7210 is preferably 0.1 to 10 g / 10 min, more preferably 0.2 to 5 g / 10 min.

[0070] When the MFR is within the above range, a desired laminate can be easily formed by a molding method such as co-extrusion molding, lamination molding, blow molding, and coinjection molding, which is preferred.

[0071] The composition of the present invention is not particularly limited as long as it contains the modified product of the present invention, and may consist only of the modified product of the present invention.

[0072] Since the composition of the present invention includes the modified product of the present invention, a layer having high bonding strength with the objects to be bonded, particularly the layer containing PPS, can be formed even in a short bonding time.

[0073] Since the modified product of the present invention has higher reactivity with polar groups present in PPS etc. than the graft modified product modified with glycidyl (meth)acrylate or acid / anhydride, the composition of the present invention containing the modified product of the present invention has significantly better adhesion with the layer containing PPS.

[0074] Since the modified product of the present invention is not a block copolymer or a random copolymer of an olefin monomer such as ethylene or propylene and the above-mentioned carbodiimide monomer but a graft modified product, the composition of the present invention can achieve the above-mentioned effects by using the modified product of the present invention.

[0075] The modified product of the present invention may be used in the composition of the present invention in the form of one species or in the form of two or more species.

[0076] The content of the modified product of the present invention in the composition of the present invention is not particularly limited, but from the perspectives of molding processability, controllability of bonding performance, economic benefits, etc., it is usually 0.5 mass% or more, preferably 1 mass% or more, and usually 60 mass% or less, preferably 50 mass% or less.

[0077] The composition of the present invention preferably contains the modified product of the present invention and one or more olefin-based polymers other than the modified product of the present invention.

[0078] The olefin polymers that can be used in the composition of the present invention are not particularly limited, and any known olefin polymers can be used as long as they are polymers made of olefins. Specifically, homopolymers or copolymers of α-olefins such as ethylene, propylene, 1-butene, 1-hexene, 4-methyl-1-pentene, and 1-octene (e.g., high-pressure low-density polyethylene, linear low-density polyethylene (LLDPE), medium-density polyethylene, high-density polyethylene, polypropylene, poly(1-butene), poly(4-methyl-1-pentene), low-crystalline or amorphous ethylene / propylene random copolymers, ethylene / 1-butene random copolymers, propylene / 1-butene random copolymers), ethylene / vinyl acetate copolymers (EVA) or saponified products thereof, ethylene / (meth)acrylic acid copolymers or metal salts thereof (ionic polymers), ethylene / cycloolefin copolymers, and polymers obtained by grafting and modifying these polymers / copolymers with polar compounds such as maleic acid and silane compounds.

[0079] Among them, in the case of the modified product of the present invention contained in the composition of the present invention, from the perspective of being able to easily obtain a composition of the present invention with excellent compatibility and better able to exert the desired effect, the above-mentioned olefin-based polymer is preferably the same polymer as the base polymer used to synthesize the modified product of the present invention.

[0080] The olefin-based polymer may be a polymer using only biomass-derived raw materials as its raw materials (eg olefins), a polymer using only fossil fuel-derived raw materials, or a polymer using both biomass-derived raw materials and fossil fuel-derived raw materials.

[0081] From the viewpoint of reducing environmental load (mainly reducing greenhouse gases), the olefin-based polymer is preferably a polymer made from a biomass-derived raw material.

[0082] In this specification, biomass-derived raw materials refer to raw materials formed from any (renewable) natural raw materials of plant or animal origin, including fungi, yeast, algae and bacteria, and their residues, such as carbon-containing 14 C isotope 1×10 ﹣12 The ratio of the raw material to the carbon content of the biomass is about 100 pMC, and the biomass carbon concentration (unit: pMC) measured according to ASTM D6866 is about 100 pMC. The raw material derived from biomass can be obtained by, for example, a conventionally known method.

[0083] For a certain polymer, when the production conditions of the polymer such as the polymerization catalyst, polymerization process, polymerization temperature, etc. are determined, even if the polymer contains biomass-derived raw materials, 14 C isotope 1×10 ﹣12 ~1×10 ﹣14 The molecular structure except for the ratio of the above proportions is equivalent to that of the polymer formed from the raw material derived from fossil fuels. Therefore, it can be considered that the performance of the polymer containing the raw material derived from biomass is the same as that of the polymer containing the raw material derived from fossil fuels.

[0084] When the composition of the present invention contains the above-mentioned olefin-based polymer, the content of the olefin-based polymer in the composition of the present invention is not particularly limited, but is usually 40% by mass or more, preferably 50% by mass or more, and usually 99.5% by mass or less, preferably 99% by mass or less, from the perspectives of molding processability, controllability of bonding performance, economic benefits, etc.

[0085] The composition of the present invention may contain various additives other than the modified product of the present invention and the above-mentioned olefin polymer as necessary within the range not impairing the purpose of the present invention.

[0086] Examples of the additive include softeners, stabilizers, fillers, antioxidants, crystal nucleating agents, waxes, thickeners, mechanical stability enhancers, leveling agents, wetting agents, film-forming aids, crosslinking agents, preservatives, rust inhibitors, pigments, dispersants, antifreeze agents, defoamers, viscosity enhancers, other thermoplastic polymers, water, and organic solvents. These additives may be used alone or in combination of two or more.

[0087] The additive may be an additive using only biomass-derived raw materials, an additive using only fossil fuel-derived raw materials, or an additive using both biomass-derived raw materials and fossil fuel-derived raw materials.

[0088] The composition of the present invention can be used in various known adhesive forms, such as water-dispersible adhesives, organic solvent-based adhesives, and hot-melt adhesives.

[0089] <Modified product of the present invention>

[0090] The modified product of the present invention is a graft modified product obtained by modifying at least one base polymer selected from polyolefins with a carbodiimide monomer having a carbodiimide group and a polymerizable double bond. In other words, it is a graft modified product in which at least one base polymer selected from polyolefins is graft-modified with a carbodiimide monomer having a carbodiimide group and a polymerizable double bond. The modified product of the present invention can also be said to be a graft modified product comprising a portion of at least one base polymer selected from polyolefins and a grafted portion derived from a carbodiimide monomer having a carbodiimide group and a polymerizable double bond.

[0091] The fact that the layer (B) contains the modified product of the present invention can be determined by infrared spectroscopy.

[0092] From the viewpoints of easy synthesis of the modified product of the present invention, easy acquisition of the graft modified product with better bonding properties, and the fact that the obtained graft modified product does not become too hard, the graft rate in the modified product of the present invention is preferably 0.3 to 7% by mass, more preferably 0.5 to 5% by mass.

[0093] The grafting rate is the quality of the structure derived from the carbodiimide monomer in the grafted modified body, which can be measured by 1 H-NMR measurement was specifically obtained by the method described in the following Examples.

[0094] [Carbodiimide monomer]

[0095] The carbodiimide monomer used for graft modification of the above-mentioned base polymer is not particularly limited as long as it is a compound having a carbodiimide group and a polymerizable double bond. However, from the perspective of better exerting the effects of the present invention, a compound represented by the following formula (1) or (2) is preferred.

[0096] The carbodiimide monomers used in the graft modification of the base polymer may be two or more, but are usually one.

[0097] The carbodiimide monomer may be a monomer derived from biomass, a monomer derived from fossil fuels, or a monomer derived from both biomass and fossil fuels.

[0098] From the viewpoint of reducing environmental load (mainly reducing greenhouse gas), the carbodiimide monomer is preferably a monomer derived from biomass or a monomer derived from biomass and fossil fuels.

[0099]

[0100] In the formula (1), R1 is a hydrogen atom or a methyl group, and is preferably a hydrogen atom from the viewpoint of easily obtaining the modified product of the present invention having a high grafting rate.

[0101] In formula (1), R2 is an alkyl group or an aryl group which may have a substituent. The alkyl group which may have a substituent may be a chain (either straight chain or branched) or may contain an alicyclic ring.

[0102] The number of carbon atoms in the alkyl group which may have a substituent is preferably 1 or more, more preferably 3 or more, preferably 20 or less, more preferably 12 or less, and further preferably 8 or less. In addition, the number of carbon atoms in the aryl group which may have a substituent is preferably 5 or more, more preferably 6 or more, preferably 20 or less, more preferably 12 or less, and further preferably 8 or less.

[0103] Examples of the substituent which the alkyl group and the aryl group may have include a halogen atom, a hydrocarbon group having 1 to 8 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, a carboxylate group having 1 to 8 carbon atoms, a sulfonate group having 1 to 8 carbon atoms, a carbonyl group having 1 to 8 carbon atoms, an amide group having 1 to 8 carbon atoms, an amino group having 1 to 8 carbon atoms, a thioether group having 1 to 8 carbon atoms, a phosphate group having 1 to 8 carbon atoms, an alkylsilyl group having 1 to 8 carbon atoms, and an alkoxysilyl group having 1 to 8 carbon atoms.

[0104] Among them, from the viewpoints of solubility and availability of the carbodiimide monomer and easy purification of the obtained graft modified product, R2 is preferably an aliphatic hydrocarbon group having 4 to 20 carbon atoms including an alicyclic ring, and more preferably an alicyclic hydrocarbon group having 5 to 7 carbon atoms.

[0105] Examples of the alicyclic ring include cyclobutane ring, cyclopentane ring, cyclohexane ring, cycloheptane ring, and the above rings having a hydrocarbon group. In addition, the alicyclic ring may be a polycyclic ring such as an adamantyl ring or a methyladamantyl ring.

[0106]

[0107] In formula (2), R3 is a hydrogen atom or a methyl group, and is preferably a methyl group from the viewpoint of easily obtaining the composition of the present invention having excellent bonding strength with the layer containing PPS.

[0108] In formula (2), R4 is an alkyl group or an aryl group which may have a substituent. The alkyl group which may have a substituent may be a chain (may be straight chain or branched) or may contain an alicyclic ring.

[0109] The number of carbon atoms in the alkyl group which may have a substituent is preferably 1 or more, more preferably 3 or more, preferably 20 or less, more preferably 12 or less, and further preferably 8 or less. In addition, the number of carbon atoms in the aryl group which may have a substituent is preferably 5 or more, more preferably 6 or more, preferably 20 or less, more preferably 12 or less, and further preferably 8 or less.

[0110] Examples of the alicyclic ring include cyclobutane ring, cyclopentane ring, cyclohexane ring, cycloheptane ring, and the above rings having a hydrocarbon group. In addition, the alicyclic ring may be a polycyclic ring such as an adamantyl ring or a methyladamantyl ring.

[0111] Examples of the substituent which the alkyl group and the aryl group may have include a halogen atom, a hydrocarbon group having 1 to 8 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, a carboxylate group having 1 to 8 carbon atoms, a sulfonate group having 1 to 8 carbon atoms, a carbonyl group having 1 to 8 carbon atoms, an amide group having 1 to 8 carbon atoms, an amino group having 1 to 8 carbon atoms, a thioether group having 1 to 8 carbon atoms, a phosphate group having 1 to 8 carbon atoms, an alkylsilyl group having 1 to 8 carbon atoms, and an alkoxysilyl group having 1 to 8 carbon atoms.

[0112] Among them, from the viewpoint of easily obtaining the composition of the present invention having excellent bonding strength with the layer containing PPS, R4 is preferably an unbranched and uncyclic alkyl group, and more preferably an unbranched and uncyclic alkyl group having 3 to 7 carbon atoms.

[0113] In addition, from the perspectives of improving the stability of the carbodiimide group in the air and during heating, improving the yield when synthesizing the modified body of the present invention, and reducing the manufacturing cost, the above-mentioned R4 is preferably a branched but ringless alkyl group, and more preferably a branched but ringless alkyl group having 3 to 7 carbon atoms.

[0114] It should be noted that, when the above R4 has no ring, the steric hindrance caused by the ring structure can be suppressed, thereby improving the reactivity of the carbodiimide group.

[0115] Preferred examples of the unbranched and ring-free alkyl group include n-propyl, n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl and n-nonyl.

[0116] Examples of the branched but ringless alkyl group include isopropyl, sec-butyl, isobutyl, tert-butyl, 1-methylbutyl, 1,2-dimethylpropyl, 2-methylbutyl, 3-methylbutyl, 1-ethylpropyl, 1,1-dimethylpropyl, 2,2-dimethylpropyl, 1-methylpentyl, 1,2-dimethylbutyl, 1,3-dimethylbutyl, 1,2,2-trimethylpropyl, 2-methylpentyl, 2,2-dimethylbutyl, butyl, 2,3-dimethylbutyl, 2-ethylbutyl, 3-methylpentyl, 3,3-dimethylbutyl, 4-methylpentyl, 1-ethyl-2-methylpropyl, 1-ethylbutyl, 1,1-dimethylbutyl, 1,1,2-trimethylpropyl, 1-ethyl-1-methylpropyl, 1-methylhexyl, 1,2-dimethylpentyl, 1,3-dimethylpentyl, 1,4-dimethylpentyl, 1,2,3-trimethylbutyl, 1, 2,2-trimethylbutyl, 1,3,3-trimethylbutyl, 2-methylhexyl, 2,3-dimethylpentyl, 2,4-dimethylpentyl, 2,3,3-trimethylbutyl, 1,1-dimethylpentyl, 1,1,2-trimethylbutyl, 1,1,3-trimethylbutyl, 1,1,2,2-tetramethylpropyl, 2,2-dimethylpentyl, 2,2,3-trimethylbutyl, 3-methylhexyl, 3,4-dimethylpentyl, 3 ,3-dimethylpentyl, 1-ethylpentyl, 1-ethyl-2-methylbutyl, 1-ethyl-3-methylbutyl, 1-ethyl-2,2-dimethylpropyl, 2-ethylpentyl, 2-ethyl-3-methylbutyl, 1-ethyl-1-methylbutyl, 1-ethyl-1,2-dimethylpropyl, 3-ethylpentyl, 1,1-diethylpropyl, 2,2-diethylpropyl, 1-propylbutyl, diisopropylmethyl, 1-isopropylbutyl.

[0117] In formula (2), m is an integer of 2 or more, and is preferably an integer of 2 to 6, more preferably an integer of 2 to 4, and particularly preferably 2, from the viewpoints of solubility and availability of the carbodiimide monomer, and ease of purification of the obtained graft modified product.

[0118] [Base polymer]

[0119] The base polymer before being graft-modified with the carbodiimide monomer is at least one polymer selected from polyolefins.

[0120] Specific examples of the olefin include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, and 4-methyl-1-pentene.

[0121] The polyolefin may be a homopolymer of these olefins, a copolymer of two or more of these olefins, or a copolymer of one or more of these olefins and one or more of the following comonomers. The polyolefin is preferably at least one polymer selected from ethylene polymers, propylene polymers and butene polymers. When a solvent is used in the grafting reaction, it is more preferably at least one polymer selected from ethylene polymers and propylene polymers from the perspectives of excellent solubility in the solvent and excellent separation from impurities after the grafting reaction.

[0122] The base polymer of the modified product of the present invention may be two or more types, but is usually one type.

[0123] From the viewpoint of better exerting the effects of the present invention, the base polymer is preferably a polymer that does not contain at least one group containing activated hydrogen selected from the group consisting of a carboxyl group, an acid anhydride group, an amino group, a hydroxyl group, and a thiol group.

[0124] In addition, from the perspective of better exerting the effects of the present invention, the above-mentioned base polymer is also preferably a polymer that does not contain carboxylic acid derivative groups such as acyl halides, amides, imides, esters, and groups such as epoxy groups that are easily converted into groups with activated hydrogen by water, etc.

[0125] From the viewpoint of easy synthesis of the modified product of the present invention, the weight average molecular weight (Mw) of the base polymer is not limited but is preferably 100,000 or more, more preferably 150,000 or more, and preferably 1,000,000 or less, more preferably 700,000 or less.

[0126] For the same reason, the number average molecular weight (Mn) of the base polymer is also not limited but is preferably 40,000 or more, more preferably 50,000 or more, and is preferably 500,000 or less, more preferably 300,000 or less.

[0127] The molecular weight distribution (Mw / Mn) of the base polymer is not limited but is preferably 1.5 or more, more preferably 2.0 or more, and is preferably 6.0 or less, more preferably 5.0 or less.

[0128] The above-mentioned Mw and Mn are values ​​measured using HLC-8321GPC / HT gel permeation chromatograph (GPC) manufactured by Tosoh Corporation under the following conditions.

[0129] Separation columns: TSKgel GMH6-HT (2 columns) and TSKgel GMH6-HTL (2 columns) (both 7.5 mm I.D. × 30 cm, manufactured by Tosoh Corporation, Japan)

[0130] Column temperature: 140°C

[0131] Mobile phase: o-dichlorobenzene (containing 0.025% butylated hydroxytoluene (BHT))

[0132] Development rate: 1.0mL / min

[0133] Sample concentration: 0.1% (w / v)

[0134] Sample injection volume: 0.4mL

[0135] Detector: Differential refractometer

[0136] Equipment calibration: Calibrated using monodisperse polystyrene (#3std set manufactured by Tosoh Corporation, Japan)

[0137] The base polymer can be synthesized by a conventionally known method, or a commercially available product can be used.

[0138] As the above-mentioned conventional known methods, there are no restrictions, but for example, methods using a coordination polymerization catalyst system containing a transition metal can be cited. Specifically, a method of synthesizing by polymerizing or copolymerizing olefins such as ethylene and propylene with the following comonomers as required in the presence of a catalyst such as a magnesium chloride-supported titanium catalyst, a vanadium-based catalyst containing a soluble vanadium compound and an alkylaluminum halide, or a metallocene catalyst containing a metallocene compound and an organic aluminum oxide compound can be cited.

[0139] The raw materials of the base polymer (for example, olefins and monomers such as the comonomer described below) may be only biomass-derived raw materials, only fossil fuel-derived raw materials, or both biomass-derived raw materials and fossil fuel-derived raw materials.

[0140] From the viewpoint of reducing environmental load (mainly reducing greenhouse gases), the base polymer is preferably a polymer made from a biomass-derived raw material.

[0141] [Ethylene polymers]

[0142] Above-mentioned ethylene-based polymer is not particularly limited, as long as the structural unit content in ethylene source in this polymkeric substance is the polymkeric substance more than 50 mass %, can be ethylene homopolymer, also can be the multipolymer of ethylene and comonomer.In the situation of multipolymer, its structure is not particularly limited.

[0143] Examples of the comonomer include at least one monomer selected from propylene, α-olefins having 4 to 20 carbon atoms, and conjugated polyenes. Among them, propylene and α-olefins having 4 to 20 carbon atoms are preferred.

[0144] The α-olefins having 4 to 20 carbon atoms may be linear or branched, and examples thereof include 1-butene, 2-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene.

[0145] From the perspectives such as pellets, powders, etc., which are not easy to agglomerate, easy to handle, the content of the structural unit in the above-mentioned comonomer source in the above-mentioned ethylene polymer is preferably below 50 mass %, more preferably below 30 mass %, particularly preferably below 20 mass %. It should be noted that the content of the structural unit in propylene source and butene source, etc. is 50 mass % ethylene polymer, which is also referred to as ethylene polymer in this manual.

[0146] [Propylene polymer]

[0147] The propylene polymer is not particularly limited as long as the content of the structural unit derived from propylene in the polymer is more than 50% by mass, and can be a propylene homopolymer or a copolymer of propylene and a comonomer. The structure of these (co)polymers is not particularly limited.

[0148] Examples of the comonomer include at least one monomer selected from ethylene, α-olefins having 4 to 20 carbon atoms, and conjugated polyenes. Among them, ethylene and α-olefins having 4 to 20 carbon atoms are preferred.

[0149] Examples of the α-olefin having 4 to 20 carbon atoms include the same α-olefin having 4 to 20 carbon atoms as mentioned above in the section of the ethylene-based polymer.

[0150] From the perspective of pellets, powders, etc., which are not prone to agglomeration and easy handling, the content of the structural unit derived from the comonomer in the propylene polymer is preferably 50% by mass or less, more preferably 30% by mass or less, and particularly preferably 20% by mass or less. It should be noted that the propylene polymer having a content of 50% by mass of the structural unit derived from butene is also referred to as a propylene polymer in this specification.

[0151] [Butene polymer]

[0152] The butene polymer is not particularly limited, as long as the content of structural units derived from butene in the polymer is more than 50% by mass, and can be a homopolymer of butene, especially 1-butene, or a copolymer of butene (especially 1-butene) and a comonomer. The structure of these (co)polymers is not particularly limited.

[0153] Examples of the comonomer include at least one monomer selected from ethylene, propylene, α-olefins having 5 to 20 carbon atoms, and conjugated polyenes. Among them, ethylene, propylene, and α-olefins having 5 to 20 carbon atoms are preferred.

[0154] Examples of the α-olefin having 5 to 20 carbon atoms include the same α-olefin having 5 to 20 carbon atoms as mentioned above in the section of the ethylene-based polymer.

[0155] From the viewpoint of preventing pellets, powders, etc. from agglomerating and being easy to handle, the content of the structural unit derived from the comonomer in the butene-based polymer is preferably 50% by mass or less, more preferably 30% by mass or less, and particularly preferably 20% by mass or less.

[0156] <Method for synthesizing the modified product of the present invention>

[0157] There is no particular limitation on the method for synthesizing the modified product of the present invention, as long as a grafted modified product can be obtained after the base polymer is grafted and modified by the carbodiimide monomer. However, from the perspective of being able to easily synthesize the modified product of the present invention, it is preferred to add a free radical initiator and the carbodiimide monomer to a solution or dispersion obtained by dissolving or dispersing the base polymer in a solvent, and more preferably to a solution obtained by dissolving the base polymer in an organic solvent to react (grafting reaction). It should be noted that in the case of using a reaction device with a stirring capability that allows the base polymer to flow evenly, a solvent may not be used.

[0158] By initiating graft polymerization by the above method, a graft-modified product can be obtained.

[0159] From the perspectives of being able to easily obtain the modified product of the present invention having a grafting rate within the above-mentioned range and being able to suppress the formation of the polymer of the carbodiimide monomer itself (hereinafter also referred to as "non-grafted polymer"), the amount of the carbodiimide monomer used in the above-mentioned grafting reaction is preferably 10 to 1000 mol, more preferably 10 to 800 mol relative to 1 mol of the base polymer.

[0160] Examples of the free radical initiator include organic peroxides and azo compounds, and specific examples include benzoyl peroxide, dichlorobenzoyl peroxide, diisopropylbenzene peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di(peroxybenzoate)-3-hexyne, 1,4-di(tert-butylperoxide isopropyl)benzene, lauroyl peroxide, tert-butyl peracetate, 2,5-dimethyl-2,5-di(tert-butylperoxide)- Organic peroxides such as 3-hexyne, 2,5-dimethyl-2,5-di(tert-butyl peroxide)hexane, tert-butyl perbenzoate, tert-butyl perphenylacetate, tert-butyl perisobutyrate, tert-butyl persecanoate, tert-butyl peroxypivalate, isopropyl peroxypivalate, tert-butyl peroxydiethylacetate, tert-butyl peroxyisopropyl monocarbonate (tert-butyl peroxyisopropyl monocarbonate); azo compounds such as azobisisobutyronitrile and dimethyl azobisisobutyrate. Among them, organic peroxide compounds such as diisopropyl peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di(tert-butyl peroxide)-3-hexyne, 2,5-dimethyl-2,5-di(tert-butyl peroxide)hexane, 1,4-di(tert-butyl peroxideisopropyl)benzene, and tert-butyl peroxyisopropyl monocarbonate are preferred.

[0161] The above-mentioned radical initiators may be used alone or in combination of two or more.

[0162] From the perspective of being able to efficiently initiate the grafting reaction and easily obtain the modified product of the present invention with a grafting rate within the above-mentioned range, the amount of the free radical initiator used in the above-mentioned grafting reaction is preferably 0.01 mol or more, more preferably 0.05 mol or more, and preferably 0.7 mol or less, more preferably 0.5 mol or less relative to 1 mol of the carbodiimide monomer.

[0163] As the above-mentioned organic solvent, it is preferred that the organic solvent does not significantly hinder the grafting reaction of the above-mentioned carbodiimide monomer and has affinity with the base polymer in the temperature range where the grafting reaction is carried out. Specific examples of such organic solvents include aromatic hydrocarbon solvents such as benzene, toluene, and xylene; aliphatic hydrocarbon solvents such as pentane, hexane, heptane, octane, nonane, and decane; alicyclic hydrocarbon solvents such as cyclohexane, methylcyclohexane, and decalin; chlorinated hydrocarbon solvents such as chlorobenzene, dichlorobenzene, trichlorobenzene, dichloromethane, chloroform, carbon tetrachloride, and tetrachloroethylene; alcohol solvents such as methanol, ethanol, n-propanol, isopropanol, n-butanol, sec-butanol, and tert-butanol; ketone solvents such as acetone, butanone, and methyl isobutyl ketone; ester solvents such as ethyl acetate and dimethyl phthalate; and ether solvents such as dimethyl ether, diethyl ether, di-n-pentyl ether, tetrahydrofuran, and dihydroxyanisole. In addition, water can also be used as a solvent for suspension polymerization or emulsion polymerization. These solvents may be used alone or in combination of two or more. It is preferred that the reaction liquid be homogeneous by using these solvents, but a plurality of heterogeneous phases may be formed.

[0164] In order to carry out the graft reaction in a region where the liquid containing the base polymer can be uniformly stirred, the concentration of the base polymer in the liquid is usually set to 50 to 500 g / L, and preferably to 200 to 500 g / L to achieve a high grafting rate.

[0165] Although the radical initiator and the carbodiimide monomer can be added to the liquid containing the base polymer (or the base polymer itself) at once to initiate the grafting reaction, in order to achieve a high grafting rate, it is preferred to add them successively over a period of about 0.1 to 5 hours to carry out the grafting reaction.

[0166] It should be noted that, when the free radical initiator and the carbodiimide monomer are added to the base polymer or to a liquid obtained by dissolving or dispersing the base polymer in a solvent, there is no particular restriction on the order in which these additives are added. For example, when they are added one by one as described above, the free radical initiator and the carbodiimide monomer may be added one by one, or the free radical initiator may be added one by one after the carbodiimide monomer is added first.

[0167] The grafting reaction is usually carried out at a temperature of 60°C or higher, preferably 100°C or higher, usually 200°C or lower, preferably 160°C or lower, for usually 2 hours or more, preferably 3 hours or more, usually 10 hours or less, preferably 8 hours or less.

[0168] The modified product of the present invention obtained by the above grafting reaction can be purified and separated by known methods such as filtration, centrifugal separation, reprecipitation and / or washing to remove the used solvent, unreacted free radical initiator and carbodiimide monomer, and by-product non-grafted polymer.

[0169] In this case, from the perspective of easily obtaining the present invention composition having the above-mentioned better bonding performance, it is necessary to purify and isolate the modified product of the present invention so that the content of the non-grafted polymer contained in the modified product is preferably 5 mass % or less, more preferably 2 mass % or less.

[0170] <Method for producing laminate of the present invention>

[0171] The manufacturing method of the above-mentioned laminate varies depending on the shape, size, required physical properties, etc. of the final product, so there is no particular limitation. However, from the perspective of being able to easily manufacture the laminate of the present invention having the required physical properties of excellent interlayer adhesion, it is preferred to manufacture it by a method comprising step 1 of co-extrusion molding, lamination molding, blow molding or co-injection molding of a resin composition containing PPS and the above-mentioned composition of the present invention, and it is more preferred to manufacture it by a method comprising a co-injection molding step. In particular, according to a certain embodiment of the present invention, a laminate with excellent bonding strength can be manufactured even in a very short bonding time, so from the perspective of better exerting the effects of the present invention, it is preferred to manufacture the laminate by high-speed molding.

[0172] As the co-extrusion molding, lamination molding, blow molding and coinjection molding, any conventionally known method may be employed.

[0173] The temperature during production of the laminate is preferably 180 to 300°C, more preferably 200 to 250°C.

[0174] Since the laminate includes the layer (B), a laminate having excellent bonding strength can be easily obtained even if the time in the laminate production process is short, specifically, 7 seconds or less, preferably 5 seconds or less.

[0175] Examples of the lamination molding include the following methods (1) and (2).

[0176] (1) A method of heat-sealing the preformed layers (A) and (B) at a temperature higher than the melting temperature of at least one of the preformed layers (A) and (B) using a roll forming device, a compression forming device or the like.

[0177] (2) A method of heat-fusion bonding a preformed layer (A) or layer (B) to another layer obtained by extrusion molding or calendar molding.

[0178] When a laminate is manufactured by pressing (thermal bonding) the preformed layer (A) and layer (B) using the compression molding device in the above-mentioned method (1), when thermal bonding is performed at a temperature of, for example, 230°C, a layer with excellent bonding strength can be formed even if the thermal bonding time is set to a short time of preferably less than 20 seconds, more preferably less than 10 seconds, and further preferably less than 5 seconds.

[0179] Examples of the co-extrusion molding include a method in which a resin composition containing PPS and the composition of the present invention are simultaneously extruded using a multilayer extrusion molding apparatus to form heat-fused layers (A) and (B).

[0180] Examples of the coinjection molding include a method in which a resin composition containing molten PPS and a molten composition of the present invention are injected into a mold or the like simultaneously or at different injection times (eg, double injection molding, sandwich injection molding).

[0181] Example

[0182] Hereinafter, an embodiment of the present invention will be described based on examples, but the present invention is not limited to these examples.

[0183] <Method for measuring grafting rate>

[0184] Using an AVANCE IIIcryo-500 nuclear magnetic resonance apparatus (500 MHz) manufactured by Bruker Biospin Co., Ltd., under the measurement conditions of 1,1,2,2-tetrachloroethane-d2 as the measurement solvent, 120°C as the measurement temperature, 20 ppm as the spectrum width, 7.0 seconds as the pulse period, and 5.00 μsec as the pulse width (45° pulse), the following graft polymers obtained in the synthesis example were obtained: 1 H-NMR spectrum. In the obtained spectrum, the grafting rate of the grafted polymer obtained in the following synthesis example was calculated based on the peak intensity ratio of the protons from the hydrocarbon groups bonded to the carbodiimide groups present at 3.0 ppm to 4.0 ppm and the protons from all hydrocarbon groups bonded to the base polymer present at 0.3 ppm to 2.5 ppm.

[0185] [Synthesis example 1]

[0186] In a 1L autoclave, 25.0g of LLDPE (base polymer, comonomer species: 1-hexene, comonomer amount: 1.6% by mass, Mw: 164,000, Mn: 63,000, Mw / Mn: 2.60) and 150mL of toluene were added, and the autoclave was purged with nitrogen and sealed. Then, the internal temperature of the autoclave was raised to 140°C, and while maintaining this temperature, a double anchor stirring blade was used to stir at a stirring speed of 400rpm, and 28.1mmol of vinylphenylcyclohexylcarbodiimide and 2.2mmol of diisopropylbenzene peroxide (PERCUMYL D, manufactured by NOF Corporation) were added over two hours. Then, after stirring for another two hours, 250mL of toluene was added over 15 minutes to dilute the reaction solution.

[0187] The internal temperature of the autoclave was then cooled to 50°C, and after the pressure was removed, the slurry-like reaction liquid was taken out. 400 mL of acetone was added to the obtained reaction liquid, and after stirring for 10 minutes, the stirred liquid was filtered to separate into a solid component and a filtrate. The steps from adding acetone to filtering were repeated twice for the obtained solid component. Through these three filtrations, unreacted vinylphenylcyclohexylcarbodiimide and homopolymers of vinylphenylcyclohexylcarbodiimide were removed.

[0188] The solid component after the third filtration was dried in a vacuum dryer at 70° C. for 10 hours to obtain 25.71 g of a graft polymer (P-1). The graft ratio was 2.7% by mass.

[0189] [Synthesis example 2]

[0190] 25.0 g of polypropylene (base polymer, Mw: 313,000, Mn: 70,800, Mw / Mn: 4.42) and 110 mL of xylene were added to a 500 mL separatory bottle, and after replacing the separatory bottle with nitrogen, the internal temperature was raised to 120° C., and while maintaining the temperature, 28.1 mmol of vinylphenylcyclohexylcarbodiimide was added, and then, while stirring at a stirring speed of 400 rpm using a double anchor stirring blade, 2.2 mmol of tert-butyl peroxyisopropyl monocarbonate (PERBUTYL I, manufactured by NOF Corporation) dissolved in 10 mL of xylene was added over 10 minutes. Then, after stirring for another 3 hours, 200 mL of xylene was added to dilute the reaction solution.

[0191] The internal temperature of the separatory bottle was then cooled to 50°C, and the slurry-like reaction liquid was taken out. 400 mL of acetone was added to the obtained reaction liquid, and after stirring for 10 minutes, the stirred liquid was filtered to separate into a solid component and a filtrate. The obtained solid component was repeated three times from the addition of acetone to the filtration process. Through these four filtrations, unreacted vinylphenylcyclohexylcarbodiimide and homopolymers of vinylphenylcyclohexylcarbodiimide were removed.

[0192] The solid component after the fourth filtration was dried in a vacuum dryer at 90° C. for 10 hours to obtain 25.13 g of a graft polymer (P-2) with a graft rate of 1.5% by mass.

[0193] [Synthesis example 3]

[0194] 25.0 g of LLDPE (the same polymer as the base polymer used in Synthesis Example 1) and 110 mL of xylene were added to a 500 mL glass container, the inside of the container was replaced with nitrogen, and then the internal temperature of the container was raised to 120° C. While maintaining the temperature, 35.0 mmol of ethyl tert-butylcarbodiimide of methacrylate was added, and then the mixture was stirred at a stirring speed of 400 rpm using a double anchor stirring blade, and 2.2 mmol of tert-butyl peroxyisopropyl monocarbonate (PERBUTYL I, manufactured by NOF Corporation) dissolved in 10 mL of xylene was added over 10 minutes. Then, after stirring for another 3 hours, 200 mL of xylene was added to dilute the reaction solution.

[0195] The internal temperature of the container was then cooled to 50°C, and the slurry-like reaction liquid was taken out. 400 mL of acetone was added to the obtained reaction liquid, and after stirring for 10 minutes, the stirred liquid was filtered to separate into a solid component and a filtrate. The steps from adding acetone to filtering were repeated three times for the obtained solid component.

[0196] The solid component after the fourth filtration was dried in a vacuum dryer at 90° C. for 10 hours to obtain 25.49 g of a graft polymer (P-3). The graft ratio was 1.7% by mass.

[0197] [Synthesis Example 4]

[0198] 15.0 g of polypropylene (the same polymer as the base polymer used in Synthesis Example 2) and 62 mL of xylene were added to a 500 mL separatory bottle, and after the separatory bottle was replaced with nitrogen, the internal temperature was raised to 120° C. While maintaining this temperature, 22.1 mmol of ethyl tert-butylcarbodiimide of methacrylate was added, and then stirred at a stirring speed of 400 rpm using a double anchor stirring blade, and 9.2 mmol of tert-butyl peroxyisopropyl monocarbonate (PERBUTYL I, manufactured by NOF Corporation) dissolved in 10 mL of xylene was added over 10 minutes. Then, after stirring for another 3 hours, 150 mL of xylene was added to dilute the reaction solution.

[0199] Then, the internal temperature of the separatory bottle was cooled to 50°C, and the slurry-like reaction liquid was taken out. 400 mL of acetone was added to the obtained reaction liquid, and after stirring for 10 minutes, the stirred liquid was filtered to separate into a solid component and a filtrate. The steps from adding acetone to filtering were repeated three times for the obtained solid component. Through these four filtrations, unreacted methacrylate ethyl tert-butyl carbodiimide and methacrylate ethyl tert-butyl carbodiimide homopolymer were removed.

[0200] The solid component after the fourth filtration was dried in a vacuum dryer at 90° C. for 10 hours to obtain 15.37 g of a graft polymer (P-4) with a graft rate of 1.3% by mass.

[0201] [Synthesis example 5]

[0202] 25.0 g of LLDPE (the same polymer as the base polymer used in Synthesis Example 1) and 110 mL of xylene were added to a 500 mL glass container, the inside of the container was replaced with nitrogen, and then the internal temperature of the container was raised to 120° C. While maintaining the temperature, 4.69 g of glycidyl methacrylate was added, and then 0.39 g of tert-butyl peroxyisopropyl monocarbonate (PERBUTYL I, manufactured by NOF Corporation) dissolved in 10 mL of xylene was added dropwise over 10 minutes while stirring at a stirring speed of 400 rpm using a double anchor stirring blade. Then, stirring was continued for another 3 hours.

[0203] Next, 250 mL of xylene was added, the internal temperature of the container was slowly cooled to 50° C., the slurry-like reaction liquid was taken out, 400 mL of acetone was added to the obtained reaction liquid, and after stirring for 10 minutes, the reaction liquid was filtered to separate into a solid component and a filtrate. The obtained solid component was washed three times with 400 mL of acetone to remove unreacted glycidyl methacrylate and homopolymer of glycidyl methacrylate.

[0204] The obtained solid component was dried in a vacuum dryer at 90° C. for 10 hours to obtain 25.95 g of a graft polymer (CP-1). The graft ratio was 2.4% by mass.

[0205] [Synthesis example 6]

[0206] 25.0 g of LLDPE (the same polymer as the base polymer used in Synthesis Example 1) and 110 mL of xylene were added to a 500 mL glass container, the inside of the container was replaced with nitrogen, and then the internal temperature of the container was raised to 120° C. While maintaining the temperature, 11 mmol of maleic anhydride was added, and then a double anchor stirring blade was used to stir at a stirring speed of 400 rpm, and 0.8 mmol of tert-butyl peroxyisopropyl monocarbonate (PERBUTYL I, manufactured by NOF Corporation) dissolved in 10 mL of xylene was added over 10 minutes. Then, stirring was continued for another 3 hours.

[0207] Next, 200 mL of xylene was added, the internal temperature of the container was slowly cooled to 50°C, and then the slurry-like reaction liquid was taken out. 400 mL of acetone was added to the obtained reaction liquid, and after stirring for 10 minutes, the reaction liquid was filtered to separate into a solid component and a filtrate. The obtained solid component was washed three times with 400 mL of acetone to remove unreacted maleic anhydride.

[0208] The obtained solid component was dried in a vacuum dryer at 90° C. for 10 hours to obtain 25.17 g of a graft polymer (CP-2). The graft ratio was 0.71% by mass.

[0209] [Synthesis Example 7]

[0210] 25.0 g of polypropylene (the same polymer as the base polymer used in Synthesis Example 2) and 110 mL of xylene were added to a 500 mL glass container, the inside of the container was replaced with nitrogen, and then the internal temperature of the container was raised to 120° C. While maintaining the temperature, 33.4 mmol of maleic anhydride was added, and then a double anchor stirring blade was used to stir at a stirring speed of 400 rpm, and 2.2 mmol of tert-butyl peroxyisopropyl monocarbonate (PERBUTYL I, manufactured by NOF Corporation) dissolved in 10 mL of xylene was added dropwise over 10 minutes. Then, stirring was continued for another 3 hours.

[0211] Next, 200 mL of xylene was added, the internal temperature of the container was slowly cooled to 50°C, and then the slurry-like reaction liquid was taken out. 400 mL of acetone was added to the obtained reaction liquid, and after stirring for 10 minutes, the reaction liquid was filtered to separate into a solid component and a filtrate. The obtained solid component was washed three times with 400 mL of acetone to remove unreacted maleic anhydride.

[0212] The obtained solid component was dried in a vacuum dryer at 90° C. for 10 hours to obtain 25.01 g of a graft polymer (CP-3). The graft ratio was 0.62% by mass.

[0213] <mfr>

[0214] The MFR (g / 10 min) of the bonding compositions obtained in the following Examples and Comparative Examples was measured under the conditions of 190° C. and a load of 2.16 kg in accordance with JIS K 7210.

[0215] <Carbodiimide Group Content>

[0216] The carbodiimide group content (mmol) per 100 g of the bonding compositions obtained in the following Examples and Comparative Examples was calculated by the following formula (I). The results are shown in Tables 1 and 2 as carbodiimide group content (mmol / 100 g).

[0217] (Grafting ratio of grafted modified body used in the bonding composition [mass %] / molecular weight of carbodiimide monomer used in the synthesis of the grafted modified body) × 100 × amount of grafted modified body used in the bonding composition [mass %] / 10 (I)

[0218] <density>

[0219] The density (g / cm 3 ) was measured in accordance with JIS K7210. The results are shown in Tables 1 and 2.

[0220] [Example 1]

[0221] 11 parts by mass of the graft polymer (P-1) prepared in Synthesis Example 1 and 89 parts by mass of LLDPE (the same polymer as the base polymer used in Synthesis Example 1) were kneaded using a grinder (LABO PLASTOMILL) at a temperature of 190°C, a screw speed of 60 rpm, and a kneading time of 10 minutes to obtain a bonding composition C-1.

[0222] The MFR (190°C, 2.16 kg load) of the obtained bonding composition C-1 was 2.7 g / 10 min, and the density was 0.903 g / cm 3 The carbodiimide content in each 100 g of the composition is 1.3 mmol.

[0223] [Example 2]

[0224] A bonding composition C-2 was obtained in the same manner as in Example 1 except that 12 parts by mass of the graft polymer (P-2) produced in Synthesis Example 2 and 88 parts by mass of polypropylene (the same polymer as the base polymer used in Synthesis Example 2) were used.

[0225] The MFR (190°C, 2.16 kg load) of the obtained bonding composition C-2 was 0.6 g / 10 min, and the density was 0.893 g / cm 3 The carbodiimide content in each 100 g of the composition is 0.8 mmol.

[0226] [Example 3]

[0227] A bonding composition C-3 was obtained in the same manner as in Example 1 except that 16 parts by mass of the graft polymer (P-3) produced in Synthesis Example 3 and 84 parts by mass of LLDPE (the same polymer as the base polymer used in Synthesis Example 1) were used.

[0228] The density of the obtained bonding composition C-3 was 0.902 g / cm 3 The carbodiimide content in each 100 g of the composition is 1.3 mmol.

[0229] [Example 4]

[0230] A bonding composition C-4 was obtained in the same manner as in Example 1 except that 13 parts by mass of the graft polymer (P-4) produced in Synthesis Example 4 and 87 parts by mass of polypropylene (the same polymer as the base polymer used in Synthesis Example 2) were used.

[0231] The MFR (190°C, 2.16 kg load) of the obtained bonding composition C-4 was 2.0 g / 10 min, and the density was 0.892 g / cm 3 The carbodiimide content in each 100 g of the composition is 0.8 mmol.

[0232] [Comparative Example 1]

[0233] A bonding composition CC-1 was obtained in the same manner as in Example 1 except that 8 parts by mass of the graft polymer (CP-1) produced in Synthesis Example 5 and 92 parts by mass of LLDPE (the same polymer as the base polymer used in Synthesis Example 1) were used.

[0234] The MFR (190°C, 2.16 kg load) of the obtained bonding composition CC-1 was 2.9 g / 10 min, and the density was 0.904 g / cm 3 The epoxy group content of each 100 g of the composition was 1.3 mmol, and the composition did not contain a graft modified product modified by a carbodiimide monomer.

[0235] [Comparative Example 2]

[0236] A bonding composition CC-2 was obtained in the same manner as in Example 1 except that 18 parts by mass of the graft polymer (CP-2) produced in Synthesis Example 6 and 82 parts by mass of LLDPE (the same polymer as the base polymer used in Synthesis Example 1) were used.

[0237] The MFR (190°C, 2.16 kg load) of the obtained bonding composition CC-2 was 2.8 g / 10 min, and the density was 0.902 g / cm 3 The acid anhydride group content in 100 g of the composition was 1.3 mmol, and the composition did not contain a graft modified product modified by a carbodiimide monomer.

[0238] [Comparative Example 3]

[0239] A bonding composition CC-3 was obtained in the same manner as in Example 1 except that 13 parts by mass of the graft polymer (CP-3) produced in Synthesis Example 7 and 87 parts by mass of polypropylene (the same polymer as the base polymer used in Synthesis Example 2) were used.

[0240] The MFR (190°C, 2.16 kg load) of the obtained bonding composition CC-3 was 2.1 g / 10 min, and the density was 0.892 g / cm 3 The acid anhydride group content in each 100 g of the composition is 0.8 mmol, and the composition does not contain a graft modified body modified by a carbodiimide monomer.

[0241] <Joint Evaluation>

[0242] Preparation of pressed sheets

[0243] Each bonding composition obtained in Examples 1 to 4 and Comparative Examples 1 to 3 was press-molded under the conditions of a temperature of 180°C, a pressure of 4 MPa, a preheating time of 5 minutes, and a pressing time of 3 minutes, and then quenched in a press-molding machine set at 20°C to produce a pressed sheet with a thickness of 500 μm, a length of 80 mm, and a width of 80 mm.

[0244] Preparation of laminates

[0245] A polyphenylene sulfide (PPS) sheet (product name: TORELINA, manufactured by Toray Industries, Inc.) having a thickness of 100 μm, a length of 80 mm, and a width of 80 mm was used.

[0246] The PPS sheet, the pressed sheet and the PPS sheet are stacked in sequence, and the stacked laminate is The sheets were sandwiched and heat-bonded for 3 seconds using a heat bonding machine with the upper and lower platens set at 230°C or 250°C to produce a three-layer laminate.

[0247] Peel test

[0248] The peel strength between the PPS sheet and the pressed sheet was measured by performing T-type peeling on the upper side of the laminate (PPS sheet on the press plate (upper) side) and the pressed sheet under the conditions of a peeling environment temperature of 23°C, a peeling speed of 300 mm / min, and a peeling width of 15 mm. The results are shown in Tables 1 and 2. It should be noted that Table 1 is a record of the ethylene-based bonding composition, and Table 2 is a record of the propylene-based bonding composition.

[0249] [Table 1]

[0250]

[0251] [Table 2]

[0252] < / mfr>

Claims

1. A laminate, wherein: The invention comprises: a layer (A) containing polyphenylene sulfide and a bonding layer (B) containing a bonding composition, At least a portion of the bonding layer (B) is in contact with the layer (A), The bonding composition satisfies the following requirements (i) to (iii): (i) comprising a graft modified body formed by modifying at least one base polymer selected from polyolefins with a carbodiimide monomer having a carbodiimide group and a polymerizable double bond; (ii) containing 0.1 to 50 mmol of carbodiimide groups per 100 g of the bonding composition; (iii) Density: 0.870 to 0.940 g / cm 3 .

2. The laminate according to claim 1, wherein The carbodiimide monomer is at least one monomer selected from the group consisting of a compound represented by the following formula (1) and a compound represented by the following formula (2). In formula (1), R1 is a hydrogen atom or a methyl group, and R2 is an alkyl group or an aryl group which may have a substituent. In formula (2), R3 is a hydrogen atom or a methyl group, R4 is an alkyl group or an aryl group which may have a substituent, and m is an integer of 2 or more.

3. The laminate according to claim 1 or 2, wherein: The layer (A) is made of polyphenylene sulfide.

4. The laminate according to claim 1 or 2, wherein: The laminate is obtained by co-extrusion molding, lamination molding, blow molding or co-injection molding.

5. A method for producing a laminate, wherein: The laminate comprises: a layer (A) containing polyphenylene sulfide and a bonding layer (B) containing a bonding composition, wherein at least a portion of the bonding layer (B) is in contact with the layer (A). The manufacturing method comprises: step 1 of co-extrusion molding, lamination molding, blow molding or co-injection molding of a resin composition containing polyphenylene sulfide and the bonding composition; The bonding composition satisfies the following requirements (i) to (iii): (i) comprising a graft modified body formed by modifying at least one base polymer selected from polyolefins with a carbodiimide monomer having a carbodiimide group and a polymerizable double bond; (ii) containing 0.1 to 50 mmol of carbodiimide groups per 100 g of the bonding composition; (iii) Density: 0.870 to 0.940 g / cm 3 .

6. The method for producing a laminate according to claim 5, wherein: The carbodiimide monomer is at least one monomer selected from the group consisting of a compound represented by the following formula (1) and a compound represented by the following formula (2). In formula (1), R1 is a hydrogen atom or a methyl group, R2 is an alkyl group or an aryl group which may have a substituent, and in formula (2), R3 is a hydrogen atom or a methyl group, R4 is an alkyl group or an aryl group which may have a substituent, and m is an integer greater than 2.

7. The method for producing a laminate according to claim 5 or 6, wherein: The layer (A) is made of polyphenylene sulfide.

Citation Information

Patent Citations

  • Laminate, manufacturing method therefor, and adhesive composition

    CN108290392A

  • Hot melt adhesive resin laminate and laminate

    CN111683812A

  • Carbodiimide compound and polymer thereof, gelatinous composition, ionic conductive composition, electrochemical element, and surface-modified substrate

    JP2005048127A

  • Laminate and method for manufacturing same, and composition for adhesion

    US20180334593A1